PENGARUH KECERDASAN EMOSIONAL DAN MOTIVASI KERJA TERHADAP PENINGKATAN PROFITABILITAS PADA PT. KIEKAN MAKASSAR. - syahrul, Syahrul Mansyur (Jurnal Metaverse ADPERTISI, 2023)
The purpose of this study was to determine the effect of emotional intelligence on increasing profitability at PT Kiekan Makassar, to study the effect of providing work motivation on increasing profitability at PT Kiekan Makassar. This research approach is descriptive quantitative. Data analysis using multiple linear regression analysis. The results showed that emotional intelligence has an effect on increasing profitability at PT Kiekan Makassar. When viewed from the pattern of the relationship, the effect is positive. This means that the better the level of emotional intelligence possessed by each individual, the higher the effect on increasing profitability. Then work motivation affects the increase in profitability at PT Kiekan Makassar. This means that high employee motivation can increase profitability at PT Kiekan Makassar.